2020
DOI: 10.1108/jfra-12-2018-0118
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country determinants of IFRS for SMEs adoption

Abstract: Purpose The purpose of this study is to identify the influence of environmental and institutional factors on the adoption of the International Financial Reporting Standard for small and medium-sized entities (IFRS for SMEs). This study used the neo-institutional theory and the economic theory of networks to explain why countries choose to adopt IFRS for SMEs. Design/methodology/approach This study is based on logistic regression analysis to investigate 177 countries, including 77 jurisdictions that adopted I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 55 publications
4
36
1
1
Order By: Relevance
“…This result is in line with the argument of Ionaşcu et al [68] and the findings of several prior studies [e.g. 56,57,61,62,78,64,63]. Similarly, the results also show a positive and significant (t= 2.288, p= 0.026) relationship between LOLEBO and ADLEVL.…”
Section: Adlevl = β₀+β₁ Ininpr +ꞵ₂ Lolebo++ꞵ 3 Accedu +E (1)supporting
confidence: 92%
See 2 more Smart Citations
“…This result is in line with the argument of Ionaşcu et al [68] and the findings of several prior studies [e.g. 56,57,61,62,78,64,63]. Similarly, the results also show a positive and significant (t= 2.288, p= 0.026) relationship between LOLEBO and ADLEVL.…”
Section: Adlevl = β₀+β₁ Ininpr +ꞵ₂ Lolebo++ꞵ 3 Accedu +E (1)supporting
confidence: 92%
“…Sharairi [64] found that local institutions have significantly contributed to the adopting of IFRS by Islamic banks. Damak-Ayadi, Sassi and Bahri [63] also found that legal enforcement power has positively and significantly impacted the accounting standards adoption. Accordingly, it can be hypothesized:…”
Section: Local Legal Enforcement Bodymentioning
confidence: 92%
See 1 more Smart Citation
“…IFRS (Pichler et al, 2018). Greater practical knowledge of IFRS among foreign board members increases their acceptance (Damak-Ayadi et al, 2020).Thus, it is hypothesized that:…”
Section: International Supervisory Boardmentioning
confidence: 99%
“…However, there are no contributions verifying the determinants of voluntary IFRS adoption in Central and Eastern European (CEE) countries. Researchers focused on the determinants of voluntary IFRS adoption at a company level (Bassemir, 2018;Andre et al, 2012), at a country level (Hope et al, 2006;Pais & Bonito, 2018, Damak-Ayadi et al, 2020Salem et al, 2017;Zahid and Simga-Mugan, 2019), and both at a company and country level mostly in high developed countries. The literature does not cover the different CEO and supervisory board characteristics, which could have a potential impact on voluntary IFRS adoption.…”
Section: Introductionmentioning
confidence: 99%